KANKER LEHER RAHIM (CANCER CERVIX) SEBAGAI PEMBUNUH WANITA TERBANYAK DI NEGARA BERKEMBANG - Cahyawati Arisusilo (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2011)
Worldwide, cervical cancer is twelfth most common (Edward, 2010) and the fifth most deadly cancer in women (Globocan, 2002). It affects about 16 per 100,000 women per year and kills about 9 per 100,000 per year (WHO, 2006). Approximately 80% of cervical cancers occur in developing countries (Kent, 2010). Worldwide, in 2008, it was estimated that there were 473,000 cases of cervical cancer, and 253,500 deaths per year (NCC, 2008). Cervical cancer is the leading cause of cancer death in most developing countries (Edianto, 2006). Counted as many as 510,000 new cases occur each years and lasts more than 288,000 deaths from the disease worldwide. Low incidence of this disease in women aged under 25 years old, but the incidence increases in women aged 35 to 40 years and reached a maximum at the age of the 50's. Meanwhile, the incidence of cervical cancer it self continues to increase from about 25 per 100,000 in 1988 to around 32 per 100,000 in 1992 (Edianto, 2006).In 2005, the number of women aged 15-64 years in Indonesia is 65 million and the prevalence of cervical cancer is 50 per 100,000 women. This means the number of patients with cervical cancer is approximately 32 500 patients. Patients with stage I as much as 7% or 2275, stage Ib-IIa by 28% or 9100, and a stage IIB-IV by 65% or 21 125 patients (Rasjidi, 2007). This data showed that cancer cervix detected mostly on late stages, so it commonly called silent diseases.The uterine cervix is the lowest portion of a woman's uterus (womb). Most of the uterus lies in the pelvis, but part of the cervix is located in the vagina, where it connects the uterus with the vagina.